1978
DOI: 10.1203/00006450-197804001-00978
|View full text |Cite
|
Sign up to set email alerts
|

972 the Qt Interval in Aborted Sids Infants

Abstract: i n 7 aborted SIOS i n f a n t s were performed during sleep i n the f i r s t four months o f l i f e . The QT index (QTc) was measured with an accuracy o f 2 msec o r b e t t e r . I n contrast t o recent suggestions, the mean QTc was s i g n i f i c a n t l y smaller i n the aborted SIDS than i n the normal i n f a n t s i n both REM and q u i e t sleep (p< 0.05, unpaired t -t e s t ) . Means SD are presented: NORMAL ABORTED SIDS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gordon et al [15] demonstrated enhancement of low frequency power in the spectral graphs of SIDS infants, as compared to their control group. On the other hand, some researchers have found no significant differences when analyzing heart rate variability [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…Gordon et al [15] demonstrated enhancement of low frequency power in the spectral graphs of SIDS infants, as compared to their control group. On the other hand, some researchers have found no significant differences when analyzing heart rate variability [3,8].…”
Section: Discussionmentioning
confidence: 99%